2018
DOI: 10.21037/jgo.2018.01.18
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in major surgery for esophagogastric cancer among hospitals by case volume

Abstract: This study identified higher numbers of disparate patient factors associated with low/middle volume centers compared to high volume centers, which were associated with worse OS, and further makes the case for performance of esophagectomy and total gastrectomy at high volume centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Minorities and patients with a lower socioeconomic status may be less likely to be treated at the centers that participate in the NCDB. 34,35 The NCDB does not track complications, whether the surgery was elective or emergent, or a patient's functional or nutritional status; therefore, we are unable to ascertain the specific reasons for low compliance in this article. In addition, we can only hypothesize that an increase in integrated cancer networks may improve compliance on the basis of these retrospective data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minorities and patients with a lower socioeconomic status may be less likely to be treated at the centers that participate in the NCDB. 34,35 The NCDB does not track complications, whether the surgery was elective or emergent, or a patient's functional or nutritional status; therefore, we are unable to ascertain the specific reasons for low compliance in this article. In addition, we can only hypothesize that an increase in integrated cancer networks may improve compliance on the basis of these retrospective data.…”
Section: Discussionmentioning
confidence: 99%
“…Although the nationwide experience and large sample size provided by the NCDB PUF provide unique benefits, there are also significant limitations to this study. Minorities and patients with a lower socioeconomic status may be less likely to be treated at the centers that participate in the NCDB . The NCDB does not track complications, whether the surgery was elective or emergent, or a patient's functional or nutritional status; therefore, we are unable to ascertain the specific reasons for low compliance in this article.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we calculated the metastatic lymph nodes ratio (MLR) by dividing the number of mLN by the number of rLN. For more than 95% of patients with gastric cancer in the United States were treated in hospitals with less than 200 cases per year, we defined the SEER cohort to be from low‐volume centers 35 . Meanwhile, CIAH and PUCHI were both among the largest Asian cancer centers, and thus these cohorts were regarded to be from high‐volume centers.…”
Section: Methodsmentioning
confidence: 99%
“…Some meta-analyses suggest a benefit of centralization of esophageal cancer surgery to high-volume institutions in terms of mortality (16). Gabriel and co-authors [2018] have demonstrated that overall survival (OS) was superior for esophageal cancer patients treated at high throughput centers (17). Therefore, selection of such hospitals for NEOCRTEC5010 allowed to reduce the influence of the surgical experience on the results, providing the best possible ones.…”
Section: Editorialmentioning
confidence: 99%